Knowledge and Practices of Menstrual Hygiene among Female Secondary School Students in Iragbiji, Osun State - Oniyangi, S. O.; Oyelami, O. F. (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
Females reaching the age of puberty are supposed to be informed about menstruation and how to maintain hygienic practices during menstruation which include cleanliness, taking bath regularly during menstruation to avoid bad odour, washing of genitalia area, proper use of sanitary pads or napkins, accessibility to water for washing among others. This study therefore aimed at investigating knowledge and practices of menstrual hygiene among female secondary schools students in Iragbiji, Osun State. The objectives were to (i) assess the level of knowledge about menstruation; (ii) investigate knowledge of personal hygiene (iii) examine practice of use of pad/tissue paper/other materials used during menstruation and (iv) investigate practice of proper disposal of pad/tissue paper/other materials used during menstruation. Descriptive research design of survey type was adopted for the study, the population comprised of all female students attending senior secondary schools in Irgabiji, Osun State. Proportionate sampling technique was used to select 320 female students. Self designed questionnaire was used to elicit information from the respondents; the questionnaire was validated by three experts in the Department of Health Promotion and Environmental Health Education, University of Ilorin, Ilorin. Reliability of 0.85r was obtained through split half method using Spearman Rank Order; questionnaire was administered and collected by the researcher and research assistants. Four (4) postulated hypotheses were tested using Pearson Product Moment Correlation at 0.05 alpha level.  The findings of this study reveal that: Female secondary school students in Iragbiji, Osun State do not have knowledge of menstruation. (calculated r = 0.033 < critical r = 0.095 @ df = 318) Female secondary school students in Iragbiji, Osun State do not have knowledge of personal hygiene.( calculated r = 0.037 < critical r of 0.073 @ df of 318) Female secondary school students in Iragbiji Osun State do not practice use of pad/tissue paper/other materials during menstruation as a measure of menstrual hygiene. (calculated r = 0.074 < critical r of 0.095 @ df of 318). Female secondary school students in Iragbiji, Osun State do not practice proper disposal of pad/tissue/other materials used during menstruation as a measure of menstrual hygiene. (calculated r = 0.073 < critical r of 0.095 at df 0f 318). The study concluded that female secondary school students in Iragbiji, Osun State do not have knowledge of menstruation, do not have knowledge of personal hygiene, do not practice use of pad/tissue paper/other materials during menstruation and do not practice proper disposal of materials used during menstruation. Based on the findings of the study, this study recommended that Parents should educate their female children about menstruation even before menarche; teachers should also be enlightened on how to break the silence around menstruation in school through health talk, seminars among others.